2021
DOI: 10.1590/1807-3107bor-2021.vol35.0053
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for dental caries in Latin American and Caribbean countries

Abstract: Identifying the risk factors for dental caries is vital in epidemiology and clinical practices for developing effective preventive strategies, both, at the individual and collective levels. Different causality/determination models have been proposed to understand the development process of dental caries. In the present review, we designed a model inspired by the world-known social determinants models proposed in the 90s and more recently in the 10s, wherein the contextual factors are placed more externally and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 142 publications
(179 reference statements)
0
28
0
7
Order By: Relevance
“…1 Caries risk assessment comprises of a range of factors that are not stable and also interact with one another, and a few epidemiological surveys in LACCs investigating some of the main risk factors of dental caries have corroborated the findings of previous systematic reviews. 7 Non-white ethnicity, low educational levels exhibited by the parents, low family income, availability of a health insurance scheme, and old age have been associated with higher dental caries prevalence in the LACC population. 26 Additionally, behavioral risk factors such as a cariogenic diet, high frequency of sugar intake, additional sugar consumption, and poor oral hygiene have also been associated with increased risk of dental caries in this population.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Caries risk assessment comprises of a range of factors that are not stable and also interact with one another, and a few epidemiological surveys in LACCs investigating some of the main risk factors of dental caries have corroborated the findings of previous systematic reviews. 7 Non-white ethnicity, low educational levels exhibited by the parents, low family income, availability of a health insurance scheme, and old age have been associated with higher dental caries prevalence in the LACC population. 26 Additionally, behavioral risk factors such as a cariogenic diet, high frequency of sugar intake, additional sugar consumption, and poor oral hygiene have also been associated with increased risk of dental caries in this population.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
“…Other studies carried out in the LACC population demonstrated that the saliva buffering capacity, presence of S. mutans in the saliva, presence of erupting primary and permanent molars, and enamel defects were also related to the prevalence of dental caries. 7 Previous studies have reported that the key risk factors of dental caries can occur at various stages of life. In older people, some factors that indicate a higher risk of caries include exposed root surfaces, increased root caries, gingival recession, poor oral hygiene, and lower socioeconomic levels.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Dental caries occurs due to frequent exposure of the dental biofilm to sugars, highlighting the key role that dietary carbohydrates play in disease onset and progression. 4,5 These sugars are fermented by bacteria present in the biofilm, producing acids that lead to tooth (enamel/dentine) demineralization via a physicochemical process. 6 Consequently, teeth that are exposed to periods of demineralization more frequently than remineralization, which is a naturally occurring process, exhibit increased loss of tooth minerals and subsequent development of caries lesions.…”
Section: Introductionmentioning
confidence: 99%